2002
DOI: 10.1046/j.1365-2702.2002.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke patients in nursing homes: eating, feeding, nutrition and related care

Abstract: The purpose of this study was to explore eating, feeding and nutrition among stroke patients in nursing homes as described by their nurses and by assessments. Registered Nurses were interviewed about an individual stroke patient's state of health, care needs and nursing care received and nursing records were reviewed. Information on eating, feeding and nutrition was extracted from the interviews and nursing records. A comprehensive instrument, the Resident Assessment Instrument, was also used to assess these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 52 publications
5
58
1
1
Order By: Relevance
“…Westergren and Karlsson et al (2001) found that 80% of the patients exhibited eating difficulties after a stroke pertaining to: 1) eating three-quarters or less of the food served, 2) difficulties manipulating food on the plate, 3) transport of food to the mouth, 4) sitting position, 5) aberrant eating speed, 6) manipulating food in the mouth 7) swallowing difficulties, 8) opening and/or closing the mouth, and 9) alertness. Kumlien and Axelsson (2002) showed that the majority of stroke patients living in nursing homes required some kind of help with eating, due to swallowing problems, pneumonia, forgetting to eat and poor appetite. The help needed was described as feeding assistance, adjustment of food and liquid consistencies, cutting up the food as well as supervision of the eating process.…”
Section: Nutrition and Eating Difficultiesmentioning
confidence: 99%
“…Westergren and Karlsson et al (2001) found that 80% of the patients exhibited eating difficulties after a stroke pertaining to: 1) eating three-quarters or less of the food served, 2) difficulties manipulating food on the plate, 3) transport of food to the mouth, 4) sitting position, 5) aberrant eating speed, 6) manipulating food in the mouth 7) swallowing difficulties, 8) opening and/or closing the mouth, and 9) alertness. Kumlien and Axelsson (2002) showed that the majority of stroke patients living in nursing homes required some kind of help with eating, due to swallowing problems, pneumonia, forgetting to eat and poor appetite. The help needed was described as feeding assistance, adjustment of food and liquid consistencies, cutting up the food as well as supervision of the eating process.…”
Section: Nutrition and Eating Difficultiesmentioning
confidence: 99%
“…Perry et al (2013) emphasize that Kirkevold (1997) describes a specific therapeutic dimension in stroke nursing in which there are an interpretive function focused on nurses helping patients and their relatives understand the ramifications of a stroke, and a counselling function focused on the provision of emotional support. This is related to the argument of Kumlien and Axelsson (2002), who argue that the recognition of the provision of emotional support for eating difficulties is crucial, since it regards eating as a psychosocial function and enhances quality of life post-stroke (Medin, Larson, Von Arbin, Wredling, & Tham, 2010; Perry et al, 2013a). Taking this into account, provinding the intervention Quiet Please, Protected Mealtime care is not only a matter of stopping all non-acute activity and providing patients the opportunity to eat without interruptions but also a way of getting back to basic nursing as it was defined by Nightingale and providing specific nurse-led supportive care to patients hospitalized with a neurological disease (Kirkevold, 1997; Van Ort, 1995).…”
Section: Comprehensive Understanding and Discussionmentioning
confidence: 91%
“…In Kumlien & Axelsson's (2002) study, 80% of stroke residents in nursing homes were identified as having some form of dependence in eating and yet nursing assessment of these problems was 'vague'. In this study, although it was not the most frequently cited educational need, 63.0% of care home nurses expressed a need for more input regarding nutrition and swallowing, underlining the importance of accurate observation and care planning in terms of nutritional needs (Kumlien & Axelsson 2002).…”
Section: Discussionmentioning
confidence: 99%